Syrian Newcomer Objects: A Study in Material Culture and Forced Migration - Aydin, Fulden Elif (My University, 2023)
This research explores the world of material belongings of Muslim Syrian newcomer/refugee families as they establish themselves in Canada since 2015. The study centers the cultural and emotional meanings of the material belongings by looking at both those that are brought with the newcomers and those that are left behind. It aims to shed light on how these objects hold memories and connect refugees to their cultural and personal histories while also examining the role of displacement in this context. Additionally, it investigates the different perspectives between generations by looking into how the value and meaning of belongings may alter between older and younger family members. The key questions of the study develop at the intersection of material culture and forced migration. It first examines whether material belongings hold a significant place in the everyday lives of refugees and how this reflects on their memories. Secondly, it considers if migration and the experience that comes with it alters refugees’ attachments to their material belongings and leads to changing their sentimental value over time. Thirdly, it evaluates whether the decision-making process behind what refugees choose to bring with them and what they decide to leave behind is affected under distressing circumstances. Methodologically, the study offers an alternative ethnographic approach by braiding migrant narratives with object biographies, shifting the subject of the narrative toward a demonstration of the interrelationships of persons and things.
Keywords: forced migration; material culture; objects; material belongings; newcomers; refugees; memories; object biographies; displacement